Saddam's bombmaker : the terrifying inside story of the Iraqi nuclear and biological weapons agenda - 9; Stein, Jeff. (New York : Scribner, 2000)
Dr. Khidhir Hamza explains how Saddam Hussein created nuclear and biological weapons and discusses how he plans to use them.
"A Lisa Drew book.".
Includes index.
New York Times.
Pub Weekly.
Adult
Keywords: 9; Hussein, Saddam, -- 1937-2006.; 2; Hussein, Saddam, -- 1937-2006.; United Nations. -- Special Commission on Iraq; United Nations. -- Special Commission on Iraq; Nuclear arms control -- Iraq; Nuclear weapons -- Iraq; Persian Gulf War, 1991.; Arms control -- Iraq; Military policy -- Iraq; Nuclear weapons -- Iraq; Persian Gulf War, 1991.; Iraq -- Military policy